2022
DOI: 10.1590/s1983-41952022000400003
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration of fracture prediction map using 2D digital image correlation - 2D CID

Abstract: This work aims to present a methodology for the elaboration of a deformation map in a Portland cement concrete specimen to predict fractures caused by axial compression stresses, using the technique of Digital Image Correlation - DIC 2D. For this purpose, 5 concrete specimens with compressive strength expected at 28 days fck of 40 MPa were analyzed, which were tested in the ABNT NBR 5739/2018 standard - compression test of cylindrical concrete specimens. During the test, the necessary digital images were acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Figure 6 illustrates the crack discretization and the control points on both sides of the opening. Recently, Košćak et al [29] and Assis et al [30] presented a similar methodology and concluded that it was effective in measuring relative displacements. The values of w and δ were used in the Walraven aggregate interlock simplify model (Equation 1 and 2), and transformed into shear force (V agg ), as follows:…”
Section: Test Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 6 illustrates the crack discretization and the control points on both sides of the opening. Recently, Košćak et al [29] and Assis et al [30] presented a similar methodology and concluded that it was effective in measuring relative displacements. The values of w and δ were used in the Walraven aggregate interlock simplify model (Equation 1 and 2), and transformed into shear force (V agg ), as follows:…”
Section: Test Setupmentioning
confidence: 99%
“…The moment when the opening (w) of the critical crack A2 at 97% of the maximum load (Figure 7c) and the negligible contribution of the aggregate interlock of the crack A1 at practically the same instant indicate that another shear mechanism is responsible for transmitting the shear force on the beam. The works of Cavagnis et al [8], and [30] suggest that, in shear failure, the load is initially resisted by mechanisms other than aggregate interlock. When the load application region is near the support, a secondary physical phenomenon, known as the arching action, can contribute to the direct transmission of loads to the support.…”
Section: Conventional Concrete (C0)mentioning
confidence: 99%
See 1 more Smart Citation
“…Compressive strength is the most basic and essential mechanical property of concrete and is also the key factor to consider in the design of a concrete structure. There are also corresponding empirical prediction models in the entire public data and standard specifications, which can provide the basis for the prediction based on raw materials and mixture ratio [22][23][24]. In recent years, it has aroused great interest to construct the potential relationship between the uniaxial compressive strength of concrete and its influencing factors in a new way.…”
Section: Introductionmentioning
confidence: 99%